The nonhost mycorrhizal status of weeds and its relevance to weed management in agroecology - Pagliarani, Irene; Grassi, Arianna; Agnolucci, Monica; Turrini, Alessandra; Avio, Luciano; Giovannetti, Manuela (Frontiers in Agronomy, 2025)
The implementation of agroecological practices aims at promoting productivity and reducing environmental impacts due to the excessive use of mineral fertilizers and pesticides. It relies on soil microbiota beneficial activities, such as the efficient use of water and natural soil resources and the provision of important ecosystem services. This review will focus on arbuscular mycorrhizal fungi (AMF) and their role in weed management. AMF are soil beneficial microorganisms establishing mutualistic symbiotic associations with the roots of most food crops and playing key roles in plant growth, nutrition and health. Several plant species are unable to form functional mycorrhizal symbioses (nonhost plants), lacking “symbiotic-specific” genes, as shown by genomic, transcriptomic and phylogenomic analyses. The majority of nonhost plants belong to families encompassing some of the world’s worst agricultural weed species, such as Chenopodium album, Raphanus raphanistrum, Rapistrum rugosum, Capsella bursa-pastoris and Sinapis arvensis. The nonhost mycorrhizal status entails adverse effects on nonhost weeds due to attempted fungal colonisation, leading to reduced plant survival, growth and nutrient acquisition, particularly when grown in the presence of active AMF extraradical hyphae originating from host plants. These effects have been attributed to the activation of plant root defenses diverting resources from plant growth. This review provides qualitative and quantitative data on the interactions between AMF and nonhost weeds and on the mechanisms underlying weed fitness reduction. The lack of extensive field studies highlights the need for experimental works under real crop conditions to determine whether the combination of AMF with cover crops – a weed management practice adopted in agroecology – could serve as a valuable strategy for weed control, promoting the agroecological transition towards low-input, safe, and resilient agroecosystems.